BYHW Decoction Improves Cognitive Impairments in Rats with Cerebral Microinfarcts via Activation of the PKA/CREB Pathway. (30th December 2022) - Xue, Bingjie; Ma, Bo; Yao, Yaoyao; Zhao, Aimei; Gao, Ying; Liu, Jianxun
Abstract : Cerebral microinfarcts (CMIs) are characterized by sporadic obstruction of small vessels leading to neurons death. They are associated with increased risk of cognitive impairments and may have different risk factors compared with macroinfarcts. CMIs have a high incidence and result in heavy social burden; thus, it is essential to provide reasonable treatment in clinical practice. However, there are relatively few researches on the mechanism and treatment of CMIs, and the literature is composed almost exclusively of community—or hospital based on autopsy or imageological studies focusing on elderly patients. The Bu Yang Huan Wu (BYHW) decoction, a traditional Chinese herbal formula, has long been used to treat stroke and stroke-related diseases, including cognitive impairments. We applied microsphere-induced CMI model in rats to investigate the behavioral and molecular consequences of CMIs and to determine how they were ameliorated by BYHW decoction treatment. We then used the Morris water maze, quantitative proteomics, immunohistochemistry, and other molecular assays and found that activation of the PKA/CREB pathway by BYHW decoction treatment may reverse mitochondrial dysfunction, inhibit apoptosis of hippocampal neurons, and ameliorate CMI-induced cognitive impairments in rats. Collectively, these findings confirmed the therapeutic potential of the BYHW decoction in treating cognitive impairments induced by CMIs and demonstrated a viable mechanism for its action.